#### Answer

$-t^{2}+4t+1$

#### Work Step by Step

We are given that $g(x)=-x^{2}+4x+1$. In order to evaluate the function at $x=t$, we can plug in $t$ to the function and evaluate directly.
$g(t)=-x^{2}+4x+1=-(t)^{2}+4(t)+1=-t^{2}+4t+1$

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

$-t^{2}+4t+1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.